Holistic Treatment Patterns for Underachiever Students at Madrasah Aliyah (MAN) 2 Pontianak, West Kalimantan - Wahidah, Nurul; Elmansyah, Elmansyah (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
Madrasah Aliyah Negeri (MAN) 2 Pontianak has been working hard to resolve the case of Underachiever students, from 2023 - 2025. The school implements holistic handling, which involves many parties: Class Teachers, Subject Teachers, Guidance and Counseling Teachers, Parents and Psychologists and the handling starts from the root of the problem. This kind of handling of underachiever students has not been widely carried out in other madrasas in Pontianak City. This kind of handling pattern is felt to be successful in resolving the problem of underachiever students at the school. This study aims to reveal the holistic handling pattern of Madrasah Aliyah Negeri (MAN) 2 Pontianak. This study uses a qualitative method with a descriptive-inductive approach. The data collection technique was carried out through in-depth interviews with 9 informants, namely: 3 Guidance and Counseling Teachers, 1 Principal, 2 Underachiever Students, 2 Parents of Students, and 1 Psychologist. Through the results of the in-depth interviews conducted, this study concludes as follows: 1) that the handling of Underachiever students is carried out using a holistic approach, which is centered on the Guidance and Counseling teacher; Coordination with Class Teachers and Subject Teachers, Discussion with parents of students, and Consultation with Psychologists; 2) the process of handling underachiever students is carried out by identifying, counseling, motivating, and providing other activities related to the problems of underachiever students; 3) the toughest challenge in handling underachiever students lies in the teachers who teach, where subject teachers are often unaware of the existence of underachiever students.